2018
DOI: 10.1097/md.0000000000010335
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA systematic review and meta-analysis on Chlamydia trachomatis infections in Iranian women (1986–2015)

Abstract: Background:Chlamydia trachomatis (CT) is the cause of genital tract infections in women. Some evidence has shown the role of this infection with CT in spontaneous abortions. The purpose of this study is to study the frequency of CT infection in Iranian women.Methods:This study was performed based on PRISMA guidelines. A total of 75 articles published in Google Scholar, PubMed, ISI Web of Science, Biological abs, Iranmedex, SID, and Scopus databases were found (1986–2015) using the following keywords: CT in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, part of women colonized with UU would not develop disease, and routine treatment in these asymptomatic women for UU might result in antimicrobial resistance; therefore, clinicians are more difficult to make therapy decision for asymptomatic women. The infection rate of CT (10.20%) in the present study was lower than that in Iranian women (15%), but was similar to that in Shanghai (10.13%), southeast China. The proportion of women infected with NG in this study was within the range reported in a previous meta‐analysis (0.7%‐9.9%) .…”
Section: Discussionsupporting
confidence: 61%
“…However, part of women colonized with UU would not develop disease, and routine treatment in these asymptomatic women for UU might result in antimicrobial resistance; therefore, clinicians are more difficult to make therapy decision for asymptomatic women. The infection rate of CT (10.20%) in the present study was lower than that in Iranian women (15%), but was similar to that in Shanghai (10.13%), southeast China. The proportion of women infected with NG in this study was within the range reported in a previous meta‐analysis (0.7%‐9.9%) .…”
Section: Discussionsupporting
confidence: 61%
“…The difference between the results of this study and our study is the simultaneous analysis of infection in the mother and neonate, as well as the use of two different methods for assessments. It should be noted that the results of this meta-analysis were based on the findings of previous studies on different samples, using different methods ( 20 ). Other studies have reported different results regarding the relationship between CT and preterm delivery ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, a statistics consultant surveyed all the data and analyzed the same. The quality of the articles was assessed based on the strengthening of the reporting of observational studies in epidemiology (STROBE) checklist [17].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria: Studies in Persian with English abstracts, and original articles with full text in English published from 2011 to 2020. Exclusion criteria: Low-quality studies that had not reported the desired index, review and meta-analysis studies, letter to the editor, studies that were published in languages other than English, congress abstracts, studies that were not available for the authors in abstract or full text, studies that their sampling location and time of the study was unclear, and those that their data was not clear [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation